Exploring The Relationship between Financial Awareness and Lifestyle Indulgence in Influencing Personal Finance Strategies and Investment Decisions Among Generation Z - Tanoni, Meisien Elfira; Ann, Sheryl; Amelinda, Rita (Journal of International Conference Proceedings, 2025)
This study examines the influence of financial literacy and a hedonistic lifestyle on personal financial management and investment decisions among Generation Z. Using a quantitative approach and purposive sampling technique, data were collected from 172 respondents aged 17–27 who manage their own finances and have investment experience. The data were analyzed using SmartPLS 3.0, which included tests for measurement models, structural models, and hypotheses. The results show that financial literacy and personal financial management positively and significantly affect investment decisions. On the other hand, a hedonistic lifestyle has a negative and significant impact on both personal financial management and investment behavior. The study also found that personal financial management mediates the relationship between financial literacy and investment decisions, as well as between hedonistic lifestyle and investment decisions. These findings highlight the importance of financial education and lifestyle control in improving investment outcomes among Gen Z. Encouraging better financial knowledge and responsible money habits can lead to more effective and informed investment decisions.